2017
DOI: 10.4321/s2254-28842017000400003
|View full text |Cite
|
Sign up to set email alerts
|

Caracterización del dolor en el paciente en hemodiálisis

Abstract: Objetivos: El objetivo del presente estudio fue analizar la prevalencia y las características del dolor de los pacientes en hemodiálisis. Material y Método: Se llevó a cabo un estudio observacional descriptivo y transversal en 134 pacientes (40% mujeres y edad media de 68.05±13.77 años) del área de influencia del Servicio de Nefrología del Hospital Reina Sofía de Córdoba. Para valorar las características del dolor se utilizó el Cuestionario de Dolor Español y Cuestionario Breve del Dolor. Además, se evaluó la … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
4
0
1
Order By: Relevance
“…Of these, 152 studies were excluded leaving 68 studies for inclusion in the analysis. 2,3,5,7,8,14,19,24-84 The flow chart in Figure 1 outlines this process, including reasons for exclusion. Supplemental Table S1 provides a list of excluded studies with reasons for exclusion.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, 152 studies were excluded leaving 68 studies for inclusion in the analysis. 2,3,5,7,8,14,19,24-84 The flow chart in Figure 1 outlines this process, including reasons for exclusion. Supplemental Table S1 provides a list of excluded studies with reasons for exclusion.…”
Section: Resultsmentioning
confidence: 99%
“…Details of the 68 included studies are reported in Table 2 and include data from 16 558 patients from 26 countries. Forty-eight of the studies examined 8464 hemodialysis (HD) patients from 23 countries, 5,7,8,14,24,28,29,32,34-41,43-46,49,51-56,58,59,61-63,65-68,70,72,73,75,76,78-84 3 studies from 3 countries included data from 679 peritoneal dialysis (PD) patients, 24,49,81 and 8 studies from 6 countries reported data from 3701 patients on either HD or PD (without separating treatment groups). 2,3,25,26,60,69,71,77 Two studies assessed 112 patients from Canada and the United States following the withdrawal of dialysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intradialytic pain was predominantly localized in the lower limbs (18.7%) and the lower back area (18.7%). Studies have shown higher percentages of pain in the lower limbs: around 60% in the study by Santos et al [ 17 ], 42.3% in the study by Sousa et al [ 31 ], and 47% in the study by Pozo et al [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Según el Registro de la Sociedad Española de Nefrología de 2016, la prevalencia global de la ERCA en España es de 1233,5 pacientes por millón de población, de los cuales el 42.2% está en programa de Hemodiálisis (HD). A esto hay que añadir, que más del 60% son mayores de 65 años (10).…”
Section: Introductionunclassified